A Comparative Study of Wear Effect on the Microstructures Behavior of CoNiCrAlY Coatings fabricated by APS, HVOF and CGDS Coatings - Gok, Mustafa Sabri; Karaoglanli, Abdullah Cahit; Erdogan, Azmi; Türk, Ahmet (International Conference on Plasma Surface Engineering, 2013)
This work focuses on the micro-abrasion wear and microstructural properties of CoNiCrAlY coatings fabricated on nickel based super alloy substrates by using the atmospheric plasma spraying (APS), high-velocity oxygen fuel (HVOF), cold gas dynamic spraying (CGDS) methods. Tribological tests were performed on the samples in order to understand the wear mechanism of thermally sprayed coatings and influence of the coating microstructure on wear mechanism. The microstructures of as sprayed and weared coatings were investigated by scanning electron microscopy. Initial surface topography was examined by surface profilometer. Coating hardness measurements were performed with a micro-hardness tester. The micro-abrasion tests were carried out with some different durations. The lateral fracture was observed as wear mechanism on the specimens. The wear surface resistance have changed with coating process and surface features of specimens depending on the coating process.